A meta-analysis of Lactobacillus-based probiotics for growth performance and intestinal morphology in piglets - Zhu, Cuipeng; Yao, Jiacheng; Zhu, Miaonan; Zhu, Chuyang; Yuan, Long; Li, Zhaojian; Cai, Demin; Chen, Shihao; Hu, Ping; Liu, Hao-Yu (Frontiers in Veterinary Science, 2022)
Antibiotics are widely used as growth promoters (AGPs) in livestock production to improve animal performance and health. However, pig producers today face the prohibition of in-feed antimicrobials and have to find safe and effective alternatives. Lactobacillus species are active microorganisms that convey multiple beneficial effects to the host and are one of the most promising AGPs replacements. Here, we aim to comprehensively assess the effects of Lactobacillus spp. supplementation on growth performance and intestinal morphology (villus height [VH], crypt depth [CD], and the V/C ratio) of piglets. Among the 196 identified studies, 20 met the criteria and were included in the meta-analysis. The effects of Lactobacillus-based probiotics supplementation on growth performance and intestinal morphology were analyzed using a random-effects model. And the publication bias was evaluated by funnel plots. Our results revealed that Lactobacillus spp. supplementation significantly improved the growth performance, including average daily feed intake (ADFI), average daily gain (ADG), and the gain-to-feed ratio (G/F) in piglets (P < 0.05). Meanwhile, Lactobacillus spp. remarkably increased VH and the V/C ratio (P < 0.05) in the small intestine, including the duodenum, jejunum, and ileum, which might contribute to an improved digestive capacity of these animals. In conclusion, our findings provide concrete evidence of the growth-promoting effects of Lactobacillus spp. supplementation in piglets and a better understanding of the potential of Lactobacillus-based probiotics as AGPs alternatives in pig production.